Prevalence of Anxiety and Depression in Young Patients Presenting with Atypical Chest Pain with Normal Coronaries - Ahmed, Adeel; Mehreen, Sobia; Samore, Naseer Ahmed; Iqbal, Usman; Siddique, Muhammad Bilal; Virk, Mutahir Abbas; Shahzad, Syed Khurram; Siddiqui, Abdul Hameed (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the prevalence of anxiety and depression in young patients presenting with atypical chest pain and normal coronary arteries. Study Design: Analytical, Cross-Sectional Study. Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases Rawalpindi, Pakistan, from Jul to Dec 2021. Methodology: This study was carried out on 750 participants (having normal coronaries) of both gender and age<40years divided into study group (presented with atypical chest pain; n=375) and comparison group (no chest pain; n=375). Consecutive sampling technique was applied to collect data. Hospital Anxiety and Depression Scale (HADS) Questionnaire was used. Patients scoring 11 or more out of 21 points in Depression and Anxiety scale were identified as positive. Data was analyzed using SPSS version 24:00. Chi Square test was applied to find association between variables and p-value <0.05 was taken as significant value. Results: Out of n=750 patients 619(82.4%) were males and 131(17.6%) were females. Mean age at presentation was 33.54±5.54 years and 30.93±5.68 years in study and comparison group respectively. About 230(61.3%) participants had anxiety in the study group compared with 189(50.4%) in the comparison group, which was statistically significant (p=0.003). 221(58.9%) participants in study group and 132(35.2%) in comparison group had depression (p<0.001). Conclusion: Non cardiac chest pain is a common manifestation of depression and anxiety. Early recognition and prompt referral of these patients should be ensured to improve quality of life and prevent future unnecessary hospital visits.